Chrysanthemum indicum L.: A Comprehensive Review of its Botany, Phytochemistry and Pharmacology - Shao, Yanhao; Sun, Yunda; Li, Ding; Chen, Yiping (The American journal of Chinese medicine (1979), 2020)
L. ( L.), a member of the Compositae family, is a perennial plant that has been used as a traditional medicine for more than 2000 years in China and is widely used for the treatment of Pemphigus, swelling, pain, and scrofula. To date, more than 190 chemical constituents have been isolated and identified from this plant, including flavonoids, terpenoids, phenylpropanoids, and phenolic acids. Numerous modern studies have shown that extracts or monomeric compounds from L. have several pharmacological activities, such as anti-inflammatory anti-oxidation, antipathogenic microorganism, anticancer, immune regulation, and hepatoprotective effects. However, resource availability, the research on the mechanism, and quality control are still insufficient, which deserves further efforts. In this paper, the advances in botany, phytochemistry, and pharmacology of L were reviewed. We hope that this review can provide important information for traditional Chinese medicine, phytochemistry, synthetic and medicinal chemistry researchers for making full use of L. resource.